Using mindful play to unlock creativity: A creative companion - Johanna Payton (PRISM, 2020)
In this ‘creative companion’ (a guide to my creative practice with IKEA manual-inspired illustrations) I explain the concept of ‘mindful play’, a fusion of playful and mindful learning and teaching, and how I harnessed it to design four creative interventions for use in the higher education classroom.